Secure Blockchain-Supported Cloud System for Patients' Electronic Health Record (EHR) Systems - Mızrak, Hamit; Aslan, Serpil (Fırat University, 2023)
Since many transactions worldwide are now digitalized, data security, data sharing, fast access to data, and protecting data integrity have been considered necessary. With each passing day, our dependence on computers in our daily lives and data formation in parallel with this dependence is a part of the natural whole. This large data community has also increased the importance of data security. The word that has been heard most recently about data security is blockchain. Blockchain is a public digital ledger that records transactions across multiple computers, designed to ensure secure data sharing and maintain decentralized data transaction integrity, and cannot be changed retrospectively afterward. In recent years, cloud-based Electronic Health Records (ESK) have become the focus of attention of many researchers for remote access to patient data. The accuracy and confidentiality of patient data is a significant concern in the healthcare industry. This study proposes a new blockchain-supported solution for sharing health data between cloud service providers while providing access control and control for IHC records. The proposed method aims to transition from the management and control of the patient's electronic health records by the health sector to a patient-centered application where the patients' data are in control.

Dünyada birçok işlemler artık dijitalleştiğinden dolayı veri güvenliliği, veri paylaşımı, veriye hızlı erişim, verilerin bütünlüğünü korunmak önemli görülmüştür. Her geçen gün, günlük yaşantımızda bilgisayara bağımlılığımız ve bu bağlılığa paralel olarak verilerin oluşması tamamen doğal bütünün bir parçasıdır. Oluşan bu büyük veri topluluğu beraberinde veri güvenliğinin önemini de arttırmıştır. Veri güvenli konusunda son zamanlarda en çok duyulan kelime blok zinciri kelimesidir. Blok zincir, güvenli veri paylaşımını sağlamak ve merkezi olmayan veri işlem bütünlüğünü korumak amacıyla tasarlanmış birçok bilgisayardaki işlemleri kaydeden ve daha sonra hiçbir şekilde geriye dönük olarak değiştirilemeyen halka açık dijital defterlerdir. Son yıllarda bulut tabanlı Elektronik Sağlık Kayıtları (ESK), hasta verilerine uzaktan erişim için birçok araştırmacının ilgi odağı haline gelmiştir. Hasta verilerinin doğruluğu ve gizliliği, sağlık sektöründe önemli bir endişe kaynağıdır. Bu çalışmada, ESK kayıtları için veri erişim kontrolü ve denetimi sağlarken bulut servis sağlayıcıları arasında sağlık verilerinin paylaşılması için blok zincir destekli yeni bir çözüm önerilmiştir. Önerilen yöntemle, hastanın elektronik sağlık kayıtlarının sağlık sektörü tarafından yönetilmesinden ve kontrol edilmesinden, hastaların verilerinin kontrolünde olduğu hasta merkezli bir uygulamaya geçiş hedeflenmektedir.
Hastaların Elektronik Sağlık Kayıt (ESK) Sistemleri için Güvenli Blok Zincir Destekli Bulut Sistemi
Keywords: Engineering; Mühendislik